The dynamics of change in striatal activity following updating training. Issue 7 (14th February 2012) - Kühn, Simone; Schmiedek, Florian; Noack, Hannes; Wenger, Elisabeth; Bodammer, Nils C.; Lindenberger, Ulman; Lövden, Martin
Abstract Increases in striatal activity have been suggested to mediate training‐related improvements in working‐memory ability. We investigated the temporal dynamics of changes in task‐related brain activity following training of working memory. Participants in an experimental group and an active control group, trained on easier tasks of a constant difficulty in shorter sessions than the experimental group, were measured before, after about 1 week, and after more than 50 days of training. In the experimental group an initial increase of working‐memory related activity in the functionally defined right striatum and anatomically defined right and left putamen was followed by decreases, resulting in an inverted u‐shape function that relates activity to training over time. Activity increases in the striatum developed slower in the active control group, observed at the second posttest after more than 50 days of training. In the functionally defined left striatum, initial activity increases were maintained after more extensive training and the pattern was similar for the two groups. These results shed new light on the relation between activity in the striatum (especially the putamen) and the effects of working memory training, and illustrate the importance of multiple measurements for interpreting effects of training on regional brain activity. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.